Aquafaba and Cinnamon Essential Oil for the Production of Biodegradable and Compostable Wine Vineyard Waste-Based Material - Sergio Moraga-Bustos; Yessica Rivas; Ricardo Villalobos; Marcela Jarpa-Parra (Resources)
(1) Grape stalks and aquafaba (Aq) from chickpeas are promising agricultural byproducts with potential applications in the development of sustainable biocomposite materials due to their ligno-cellulose and protein content. (2) This study aimed to evaluate the incorporation of Aq and cinnamon essential oil (CEO) into grape stalk-based materials to enhance mechanical properties and prevent microbial contamination. Four formulations were prepared, and their mechanical, physicochemical, and antifungal properties were assessed. (3) The incorporation of CEO significantly reduced water absorption, while formulations containing Aq exhibited the highest mechanical resistance, likely due to synergistic interactions between proteins and polysaccharides that modified the microstructure of cellulose fibers. Scanning electron microscopy (SEM) images supported these findings. Additionally, CEO-treated samples showed resistance to fungal contamination by Botrytis cinerea, unlike untreated samples, which were colonized by the fungus. Biodegradability tests indicated slower degradation for CEO-treated samples (10 weeks) compared to those without CEO (5–7 weeks). (4) The results suggest that the combination of Aq and CEO creates a promising material for use in food packaging, though further research is needed to fully understand the reinforcement mechanisms.